PENGOLAHAN LINDI SEBAGAI PUPUK CAIR UNTUK MENDUKUNG PENGEMBANGAN TPA SAMPAH LESTARI - Nurhasanah Nurhasanah; Latifah K Darusman; Surjono Hadi Sutjahjo; Bibiana Widiati Lay (LPPM Universitas Terbuka, 2010)
A laboratory scale research to obtain environmentally safe effluent and liquid fertilizer from leachate from Final Waste Disposal Site in Galuga owned by Regional Government of Bogor City was conducted from July 2006 through to April 2007. The experiment was initiated by aerating the leachate in 4 difference aeration rates (0, 10, 30 and 70 liters/minute) followed by processing the sediment to product the liquid fertilizer. The experiment of production liquid fertilizer was carried out by adding lime with different dosage into sediment generated from processing by aerating at 70 liters/minute followed by centrifugation process or secher. Further, the liquid fertilizer generated from such experiment was applied to chilis planting (Capsicum annum). The research found that the processing conducted by aerating at the rate 70 liters/minute was the most effective in reducing pollutant from leachate. The addition of 1000 ppm CaO or Ca(OH)2 limes in sediment from aeration is the most effective in depositing the dissolved material compared to the addition of limes in other dosage. Liquid fertilizer generated through the addition of 1000 ppm CaO have the content of N = 375,83 ppm, P = 121,44 ppm, K = 948,11 ppm, Ca = 827,20 ppm, Mg = 959,50 ppm, S = 48,53 ppm, Cu = 8,23 ppm, Zn = 30,02 ppm, Mn = 230,57 ppm, Fe = 320,95 ppm, Pb = 10,34 ppm, Cd = 7,46 ppm and Cr = 2,05 ppm. The use of liquid fertilizer generated by adding 1000 ppm CaO was the most effective in enhancing vegetation growth and production of chili. The non essential elements (Pb, Cd and Cr) in fruits from vegetation given liquid fertilizer produced from such treatment did not exceed tolerable threshold.